1983
DOI: 10.1093/auk/100.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Population Studies of the Polyandrous Spotted Sandpiper

Abstract: A color-banded population of Spotted Sandpipers (Actitis macularia) was studied over a 10-yr period on Little Pelican Island, Leech Lake, Minnesota. A total of 75 females and 107 males bred for 144 ♀ ♀ yr and 200 ♂ ♂ yr. The observed skew in the population sex ratio was due primarily to behavioral exclusion of inexperienced females. Density appeared to limit population size and productivity. Locally hatched chicks accounted for 31% and 40% of the breeding females in the final 2 yr. Females laid eggs for 1.35-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“… Heavily skewed ASRs in threatened populations may represent one end of a general correlation between population trend or density and sex ratio, the mechanism of which is unknown (though it might be related to any of the following possibilities). Such a relationship has been documented in at least one globally threatened bird, the Seychelles Magpie Robin Copsychus sechellarum (Gerlach & Le Maitre 2001), and similar patterns have been noted in other species of birds (Oring et al . 1983, Fry et al .…”
Section: Results and Reviewsupporting
confidence: 60%
See 1 more Smart Citation
“… Heavily skewed ASRs in threatened populations may represent one end of a general correlation between population trend or density and sex ratio, the mechanism of which is unknown (though it might be related to any of the following possibilities). Such a relationship has been documented in at least one globally threatened bird, the Seychelles Magpie Robin Copsychus sechellarum (Gerlach & Le Maitre 2001), and similar patterns have been noted in other species of birds (Oring et al . 1983, Fry et al .…”
Section: Results and Reviewsupporting
confidence: 60%
“…1982). A number of other species demonstrate flexible mating systems that respond causally to ASR, including Spotted Sandpiper Actitis macularia (Oring et al . 1983), Kaka Nestor meridionalis (Greene & Fraser 1998), Lesser Spotted Woodpecker Picoides minor (Wiktander et al .…”
Section: Results and Reviewmentioning
confidence: 99%
“…(Bunni 1959). In contrast, Spotted Sandpipers nest exclusively in vegetation adjacent to bodies of water and rear broods along the shorelines (Oring et al 1983). In general, Killdeer parents moved their broods over longer distances than did Spotted Sandpipers.…”
Section: Resultsmentioning
confidence: 99%
“…Spotted Sandpipers have a resource-defense polyandrous mating system (Emlen and Oring 1977). An outline of their breeding behavior is given by Oring (1982: 70-73, and references therein), and demographic aspects of the study population may be found in Oring et al (1983). Three features of reproductive biology are relevant here.…”
Section: Spotted Sandpipersmentioning
confidence: 99%
“…Polyandry leads to the limitation and even exclusion of breeding by some females. Females in our population have bred with up to four males per season, averaging 1.66 mates per breeding female between 1973(Oring et al 1983. Polyandry is advantageous for females, at least on an annual basis, since the number of chicks fledged per year increases as the number of mates increases (Oring 1982).…”
Section: Spotted Sandpipersmentioning
confidence: 99%